Practical Aspects of Auditing (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article covers the analysis of the structure and dynamics of fixed assets, auditing of fixed assets through analytical indicators, international standard financial reporting, determination of coefficients of serviceability of fixed assets, analysis of movement and wear of fixed assets.